2023
DOI: 10.1186/s13731-023-00287-y
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effect of electronic banking service quality on customer satisfaction and loyalty: an implication for technological innovation

Abstract: In this ever-growing competitive banking industry, understanding the effect of electronic banking service quality on customers’ satisfaction and loyalty is the secret to being competitive and successful in the sector. In Ethiopia, measuring service quality in the banking sector is a new paradigm. The primary purpose of this research was to examine the effect of electronic banking (e-Banking) service quality on customer satisfaction in Ethiopia’s emerging banking industry. Data were obtained using a closed-ende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
(62 reference statements)
1
18
0
Order By: Relevance
“…Amin and Isa (2008) discovered that providing greater levels of services will result in more satisfied customers. Ayinaddis et al (2023) found that customer satisfaction and system availability were both favorable and significant. However, Matar and Alkhawaldeh (2022) found no connection between perceived security issues and Wi-Fi service consumption.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Amin and Isa (2008) discovered that providing greater levels of services will result in more satisfied customers. Ayinaddis et al (2023) found that customer satisfaction and system availability were both favorable and significant. However, Matar and Alkhawaldeh (2022) found no connection between perceived security issues and Wi-Fi service consumption.…”
Section: Discussionmentioning
confidence: 98%
“…The standardized path was 0.840 for the efficiency of the website, 0.798 for e-customer service, 0.182 for userfriendliness, 0.165 for security & privacy, and 0.162 for site organization, respectively. Ayinaddis et al (2023) reported trustworthiness, security and secrecy, pace, and suitability significantly influence customer satisfaction. Matar and Alkhawaldeh (2022) also found that perceived value, ease of use, and bank credibility have a positive and significant relationship using technology services.…”
Section: Analysis and Findingsmentioning
confidence: 95%
See 3 more Smart Citations